A polymer/small-molecule binary-blend hole transport layer for enhancing charge balance in blue perovskite light emitting diodes. Issue 26 (22nd June 2022) - Yu, Zhongkai; Jeong, Woo Hyeon; Kang, Keehoon; Song, Hochan; Shen, Xinyu; Ahn, Hyungju; Lee, Seok Woo; Fan, Xiangyang; Jang, Ji Won; Ha, Su Ryong; Min, Jeong Wan; Park, Jong Hyun; et al.
Abstract : A polymer/small-molecule binary-blend hole transport layer provided balanced charge transport and efficient recombination of electrons and holes in the perovskite layer, and an optimal device based on the blended HTL shows the highest EQE of 5.30%. Abstract : Metal halide based perovskite light-emitting diodes (PeLEDs) are promising candidates for next generation commercial display products due to their excellent high color-purity and recent dramatic improvements in their device efficiencies. However, the performance of blue PeLEDs falls far short of the requirements of commercialization, for which one of the main reasons is the wide band gap of blue-emitting perovskites, resulting in inferior hole injection and imbalanced charge transport in the emissive layer. Here, we introduce a facile method for overcoming the charge balance issue by developing a polymer/small-molecule binary-blend hole transport layer (HTL) with poly(9-vinylcarbazole) (PVK) and 2-(4-biphenyl)-5-(4- tert -butylphenyl)-1, 3, 4-oxadiazole (PBD). The binary-blend HTL allows a systematic modulation of the hole injection barrier that enabled balanced charge transport between electrons and holes for an effective recombination within the perovskite emissive layer. In particular, the PeLED based on our optimal blended HTL exhibits one of the highest external quantum efficiency (EQE) values of 5.30% for blue PeLEDs with an emission peak at 478 nm. Our work provides a simple and effective concept for forming an energy ladder for efficient charge transport which will contribute towards developing high performance blue PeLEDs.